(untitled) (مجلة البحوث الأكاديمية, 2026)
This study used a solvent-free mechanochemical method as a green synthesis strategy to create two pyridine-based Schiff base ligands (H₂L₁ and H₂L₂) produced from 2,3-dihydroxybenzaldehyde. Mechanochemical grinding and microwave assistance were used to create their equivalent nickel(II) and copper(II) complexes. Using elemental analysis, FT-IR, mass spectrometry, and molar conductivity tests, the ligands and complexes were thoroughly described. Depending on the ligand structure, spectroscopic data verified ON and ONN coordination modes, resulting in octahedral and distorted octahedral geometries surrounding the metal centers. In view of their possible biological ramifications, structural characteristics were examined, laying the groundwork for further anticancer assessment.